Simulation and Performance Analysis of a Military Insignia Microstrip Patch Antenna at 2.45 GHz For Wireless Applications - SHEHU, Shehu S.; OLADIPUPO, Samuel O.; NYITAMEN, Dominic S. (FUDMA Journal of Engineering and Technology, 2026)
This study proposes a design approach for developing a patch antenna whose radiating element replicates an exact image or logo of an entity; the proposed antenna was designed using the insignia of Nigeria army military rank (colonel) as a radiator. The antenna is engineered to operate at Industrial, Scientific, and Medical (ISM) and Wi-Fi spectrum for Wireless Body Area Network (WBAN) applications at 2.45 GHz intended for wireless military and defense communication applications. The proposed antenna structure was developed by strategically substituting the conventional rectangular shape with military insignia of colonel rank as a radiator. The antenna was designed on an FR-4 substrate with dielectric constant of 4.4 and thickness of 1.6 mm. Both free space and on-body simulation was carried out using Computer Simulation Technology (CST) Microwave software. Key antenna parameters were analysed. The results showed that the free space achieved a resonant frequency of 2.457GHz, S11 is -43.465dB, VSWR is 1.013, bandwidth of 101.4MHz, directivity is 5.342dBi, the gain is 2.551dBi, maximum surface current is 7305.42 A/m, and the radiation efficiency is 52.2%, while on-body shows that the  resonant frequency is 2.473GHz, S11 is -20.81dB VSWR is 1.200, efficiency is 46.57% and most important SAR obtained is 1.64 W/Kg, the results obtained shows that the proposed antenna is suitable for military wireless communication systems, radar systems, surveillance equipment, tactical and defence wireless networks.
Keywords: Microstrip patch antenna, military insignia antenna, CST Microwave Studio, ISM Band.